ANALISIS STRATEGI PENGEMBANGAN USAHA PETERNAKAN AYAM PEDAGING BROILER DI KECAMATAN SANGIR KABUPATEN SOLOK SELATAN (STUDI KASUS PETERNAKAN AYAM PAK ILYAS KECAMATAN SANGIR - Putri Oktora Ningsih; Novera Martilova (CV. Adiba Aisha Amira, 2024)
This research was raised because for more than five years, broiler farms, or broiler chickens, were located in Sangir District, South Solok Regency. Because livestock provide a source of animal protein to the community, the livestock sector provides great business opportunities. The purpose of this study was to find and analyze the internal and external factors faced by farmers in Sangir District, South Solok Regency, and create alternative strategies for building a livestock business. The IFE, EFE, IE, and SWOT matrices are the analytical tools used. The results of the analysis of internal and external environmental strengths and opportunities show that implementing standard operating procedures (SOP) is a way to achieve the expected targets and avoid environmental impacts, maintain and increase the number of customers, plan locations for timely delivery of goods, improve stable management, and ensure goods are available at all times. In addition, giving farmers control to improve meat quality so they can compete for market share and improving livestock management systems is a combination of the weaknesses and opportunities of this strategy.